PENGARUH KUALITAS PELAYANAN BAGIAN ADMINISTRASI AKADEMIK DAN KEMAHASISWAAN (BAAK) TERHADAP TINGKAT KEPUASAN MAHASISWA PADA POLITEKNIK PARIWISATA PALEMBANG - Mirza, Tony (STIA SATYA NEGARA PALEMBANG, 2023)
This study aims to examine the effect of the service quality of the Academic and Student Administration (1) on the Level of Student Satisfaction (2) at the Palembang Tourism Polytechnic. The type of research used is the quantitative method. The results of the study are the correlation or relationship (R) value of 0.787 and R Square of 0.619 (61.9%) the remaining 38.1 is influenced by other factors and has a simple linear regression coefficient of 0.796. This means that the Service of the Academic and Student Administration Section has a positive influence on the level of Student Satisfaction.